Meeting at the Edges: Spaces, Places and Grassroots Governance Activism in Delhi - Martin Webb (South Asia Multidisciplinary Academic Journal)
Through ethnography of activist organisations promoting transparency, accountability and active citizenship, and comprising coalitions of the city’s middle classes and urban poor, this article explores the spaces in which activists from different social backgrounds meet and carry out their work. By locating the positions of meeting rooms, offices and activists’ homes in urban space, I open up a view of the everyday practices of grassroots governance initiatives aimed at producing shared citizenship. I show how Delhi’s social and spatial segregation requires that the working through of a politics of shared citizenship must necessarily take place outside, or in between, the city’s zones of exclusivity and exclusion. I also show how activist initiatives partially incorporate the urban poor into new regimes of governance and accountability by mirroring everyday processes of leadership and mediation.